Pengembangan Aplikasi Chat Bot untuk Rekomendasi Wisata - Sari, Aulia Kurnia; Febryansyah, Feby; Febriansyah, M. Yoga; Aji, Wahyu; Saifudin, Aries; Kusyadi, Irpan (Jurnal Informatika Universitas Pamulang, 2021)
The progress of information on tourist attractions at this time has not been maximized in conveying information because many tourism places still use the system manually, such as providing brochures, pamphlets, and posters for tourists who visit tourism objects. That's why researchers are trying to develop chatbot applications. The chatbot application is a programming in Artificial Intelligent designed to be able to simulate direct conversations with humans. With the chatbot application, tourists can exchange information about tourist objects by asking the system like a discussion and can make it easier for tourists who want to visit such as out of town or even in the city with the chat bot application they can also check or see where there is a nearby tourist attraction. and it's not too far, especially during this pandemic, it's better not to leave the house, if you want to go to a tourist attraction, they just need to check the chat bot application on their respective cellphones.